CONDENSOR DESIGN ANALYSIS WITH KAYS AND LONDON SURFACE DIMENSIONS - Dedik Romahadi; Nanang Ruhyat; L. B. Desti Dorion (Universitas Mercu Buana, 2020)
The use of condensers in air conditioning units is more common in large-capacity units than in ones with a smaller capacity. Air conditioning provides comfort and freshness to an air-conditioned room. It should be noted that each room has a different heat load, which affects the specifications of the condenser used. The accuracy with which appropriate condenser specifications are determined affects the performance of the air conditioner. Thus, considering how important condenser needs are, it is necessary to design condensers with optimal performance, which adhere to proven standards. To achieve this, the design of a condenser should be based on the results of the smallest condenser dimensions of three types of surfaces, as they are intended for a limited place. This condenser design uses the standard dimensions of the Kays and London charts. Data is collected by measuring the results of temperature and enthalpy of a refrigerant at desuperheating and condensation, inlet air temperature, outlet air temperature, refrigerant mass flow rate, and air mass flow rate. The results of the compact condenser design are based on existing data, which is obtained from the smallest design results. The result uses the type of Surface CF-8.72(c) with a heat transfer area of 0.259 m2, a total tube length of 9.5 m, crossing tube length 0.594 m and a pressure drop of 3778 Pascal (Pa) on the side of a tube. This design fulfills the stipulated requirements, as the pressure drop is less than the specified maximum limit in most units.